1977
DOI: 10.1177/109019817700500404
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Continuing Medical Education: A Literature Review

Abstract: The literature of continuing medical education (CME) program evaluation was reviewed and analyzed. The "State-of-the-art" of CME evaluation is depicted in a series of tables which indicate evaluation methods and results. Evaluation designs providing strong assurances of valid results were not often found. The weakness of most published evaluations limit possible conclusions about the effectiveness of CME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

1980
1980
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(26 citation statements)
references
References 25 publications
1
22
0
3
Order By: Relevance
“…While brief continuing professional education programs can increase knowledge about new practice techniques, they often fail to change the actual practice behavior of the health care provider. [18][19][20][21] This suggests that providing information alone is likely to be a relatively ineffective dissemination strategy.…”
Section: Introductionmentioning
confidence: 99%
“…While brief continuing professional education programs can increase knowledge about new practice techniques, they often fail to change the actual practice behavior of the health care provider. [18][19][20][21] This suggests that providing information alone is likely to be a relatively ineffective dissemination strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Although earlier studies evaluating the effect of traditional CME on subsequent practitioner competence have failed to establish a cause and effect relationship, reviews by Bertram & Brooks-Bertram (1977) and Lloyd & Abrahamson (1979) established methodological defects in these papers. More recent studies have demonstrated that some forms of continuing education can produce measurable changes in practitioner behaviour, Steyn (1981) and Raymond (1986).…”
Section: Introductionmentioning
confidence: 95%
“…Proponents of continuing medical education have supported an underlying assumption that a Commitment to lifetime learning should ensure that practitioners would provide better medical care as a result of increasing knowledge-and that this should lead to improved health care outcomes (Bertram & Brooks-Bertram, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…The practical result of this error appears as an almost compulsive need to evaluate (18,19,20), ignoring at times how much effort and cost can be expended to indulge the fetish of evaluation. Those who make this mistake in reasoning fail to distinguish between the outcome in a learner and an assessment of that outcome.…”
Section: F the Evaluation Fetishmentioning
confidence: 99%